Hexokinase2 controls angiogenesis in melanoma by promoting aerobic glycolysis and activating the p38‐MAPK signaling. Issue 12 (3rd July 2019) - Lu, Jingjing; Liang, Xiaofang; Gao, Ying; Fu, Guili; Shen, Qin
Abstract: In this study, we used endostatin (ES)‐induced apoptosis of endothelial cells to study the role of Hexokinase2 (HK2) in the control of angiogenesis in melanoma. Real‐time polymerase chain reaction and Western blot analysis were performed to explore the effect of HK2, lactate, and ES on the levels of caspase‐9/3, ATP, and p38/MAPK activation. ES increased the levels of caspase‐9/3 while decreasing the level of ATP, whereas ES + HK2 and lactate both restored the normal levels of caspase‐9/3 and ATP. In addition, cells transfected with HK2 short hairpin RNA1 (HK2shRNA1) and HK2shRNA2 showed an evident decrease in the levels of caspase‐9/3 along with an obvious increase in the level of ATP. Knockdown of HK2 also increased O2 consumption while decreasing the extracellular level of lactate and the phosphorylation of p38‐mitogen‐activated protein kinase (MAPK). On the other hand, the lactate treatment elevated the phosphorylation of p38‐MAPK under time‐ and concentration‐dependent manner. In the study, we clarified the role of HK2 in the control of apoptosis of ECs, which plays an important role in the angiogenesis of melanoma by promoting aerobic glycolysis and activating the p38‐MAPK signaling. Abstract : In the study, we clarified the role of Hexokinase2 in the control of apoptosis of endothelial cells, which plays an important role in the angiogenesis of melanoma by promoting aerobic glycolysis and activating the p38‐mitogen‐activated protein kinase signaling.